Multifunctionality of urban community agriculture in Belo Horizonte, Brazil practice and politics : practice and politics - Olsson, Sofie (SLU/Dept. of People and Society, 2016)
As the food system is becoming increasingly global, and the world’s population increasingly urban, food is disconnected from people and place. This causes a range of social, economic, and environmental problems such as public health issues, disruption of livelihoods, and biodiversity loss. Urban agriculture (UA) has been endorsed as a key element of local food systems, with the potential to reconnect people with their food and contribute to solving many of the problems that cities face. This thesis analyses how urban farmers themselves view the benefits of urban community gardens on individual, neighbourhood, and city scales, how these perceptions are represented in the political framing of UA, and how they can highlight potential to advance the UA agenda. The empirical data derives from a qualitative case study of urban community gardens in the city of Belo Horizonte, Brazil, where observations and semi-structured interviews were carried out with urban farmers, municipal authorities, and researchers. The data has been triangulated with secondary data from peer reviewed academic literature, reports and official documents. By analysing the research question within a framework of agroecology, systems thinking, and multifunctionality, this thesis has aimed to bring a fresh perspective to the UA setting in Belo Horizonte, and highlight how the agenda can progress. The findings show that while UA is framed as a strategy to increase the food and nutrition security of the population, urban farmers perceive the gardens as generating a wide range of social, economic, and environmental benefits on individual, community, and city scales. The findings also indicate that UA initiatives within other municipal government bodies, although targeting some of these other aspects, are not carried out in integration with the main UA programme, possibly due to the low level of intersectoral collaboration. I argue that by recognising the potential of UA within more policy areas, the UA agenda could gain new momentum. I also suggest that a framework of multifunctionality can be a useful tool to any city wishing to explore the multiple possibilities of UA, in order to better use its potential.